Shiga toxin (STX) gene analysis and verotoxigenic potentials of Escherichia coli isolated from ‘bobozi’- an indigenous Nigerian ready to eat fermented cassava chip - Enabulele, Stephen; Daniel, Ebakota (International Journal of Biological Research, 2016)
Many strains of E. coli have been identified as food borne pathogens inducing serious gastrointestinal diseases and even causing death in humans. Amongst these are those referred to as Shiga or Vero toxin producing E. coli. Bobozi is an Indigenous Nigerian ready to eat snack food made from cassava and is widely consumed in most parts of the country. The objective of this study was to Isolate and Identify E. coli from Bobozi, analyze their Shiga toxin (stx) gene profile and thereafter determine their verotoxin capabilities. A total of 248 samples of Bobozi were purchased from hawkers in the metropolis of Benin City, Edo state, Nigeria. Isolation and Identification was done using standard microbiological methods. Analysis for the presence of Shiga toxin (stx1 and stx2) genes was done using PCR technique and for their verotoxigenic potentials using tissue culture assay on Vero cells. Result of the investigation reveals that of the total 248 samples collected, 107(43.15%) had E. coli isolated from them. Total number of E. coli isolated from the 107 samples was 386.Shiga toxin gene analysis of the isolates reveal that 169(43.78%) had stx1 gene alone, 112 (29.02%) had stx2 gene alone, 3(0.78%) had both stx 1 and stx 2 genes while 102 (26.42%) had none of the two genes. Tissue culture assay on Vero cells indicate that there is a strong relationship between the presence of stx genes and their degree of cytotoxic effect on vero cells as over 80% isolates without the genes exhibited weak cytotoxic effect whereas over 80% of those with the genes exhibited more than strong cytotoxic effect.